2021
DOI: 10.1186/s13662-021-03338-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics for a diffusive mussel–algae model near a Hopf bifurcation point

Abstract: In this paper, the Hopf bifurcation and Turing instability for a mussel–algae model are investigated. Through analysis of the corresponding kinetic system, the existence and stability conditions of the equilibrium and the type of Hopf bifurcation are studied. Via the center manifold and Hopf bifurcation theorem, sufficient conditions for Turing instability in equilibrium and limit cycles are obtained, respectively. In addition, we find that the strip patterns are mainly induced by Turing instability in equilib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Their results suggested that the regular patterning in mussel beds were caused by the high mobility of algae or the low diffusion of mussels. Zhong et al [14] investigated the spatiotemporal dynamics for a diffusive mussel-algae model near a Hopf bifurcation point. They found that the strip patterns were mainly induced by Turing instability in equilibrium and spot patterns were mainly induced by Turing instability in limit cycles by numerical simulations.…”
mentioning
confidence: 99%
“…Their results suggested that the regular patterning in mussel beds were caused by the high mobility of algae or the low diffusion of mussels. Zhong et al [14] investigated the spatiotemporal dynamics for a diffusive mussel-algae model near a Hopf bifurcation point. They found that the strip patterns were mainly induced by Turing instability in equilibrium and spot patterns were mainly induced by Turing instability in limit cycles by numerical simulations.…”
mentioning
confidence: 99%